Building Entrepreneurial Interest of Scout Members Through Business Model Canvas Design Training: Membangun Minat Wirausaha Anggota Pramuka Melalui Pelatihan Desain Business Model Canvas - Bisma Widyawan; Achmad Barlian; Joni Haryanto (Academia Open, 2025)
General Background: Youth entrepreneurship is a critical strategy for fostering economic self-reliance and innovation. Specific Background: In Indonesia, the Scout Movement has increasingly integrated character and skill-building programs, offering an opportunity to embed entrepreneurial education. Knowledge Gap: Despite awareness of entrepreneurship, practical understanding and application among adolescents—especially using tools like the Business Model Canvas (BMC)—remain limited. Aims: This study aims to enhance entrepreneurial interest and competency among 17-year-old Scout members through BMC design training. Results: Conducted as a participatory workshop, the training included lectures, business site visits, group simulations, and peer assessments. The findings showed that 66.7% of participants were unfamiliar with BMC prior to the workshop, but post-training evaluations revealed improved comprehension, with peer assessment scores averaging 3.08–4.00 (out of 5), and self-ratings predominantly between 7 and 9 (out of 10). Novelty: This study contributes novel insights into the integration of entrepreneurship education within a non-formal setting, specifically through experiential and peer-based learning methods tailored for Scout members. Implications: The findings suggest that structured, interactive training using BMC can effectively cultivate entrepreneurial mindset and skills in youth, and support the strategic inclusion of business education in character-based programs like Scouting.Highlight : Hands-on BMC Training: Scout members engaged in designing business models using the Business Model Canvas to enhance entrepreneurial skills. Peer-Based Learning: Activities included peer assessment to deepen understanding through evaluation and feedback. Youth-Centered Approach: The training targeted 17-year-old Scout members, aligning with their developmental stage and promoting real-world business thinking. Keywords : Business Model Canvas, BMC, Entrepreneurship, Scout Members, Training